ジュウリョク カラ ミタ ナンキョク ノ チカ コウゾウ - 神沼, 克伊; カミヌマ, カツタダ; 溝上, 恵; ミゾウエ, メグミ; KAMINUMA, Katsutada; MIZOUE, Megumi (国立極地研究所, 1978)
P(論文) 南極大陸の地下構造について,その概略でも良いから全体像を把握する目的で,重力を用いた解析を行った.重力を用いて地下構造を求める場合,ブーゲ異常値を使う方法が一般的である.しかし,南極大陸は平均1900 mの厚い氷床に覆われており,重力測定点の氷床の厚さは不明の場合が多く,ブーゲ異常値は得られないことが多い.そこで,Δg_h=Δg_0-2πGρ(H-h)の式によりΔg_hを求めた.Δg_0はフリーエア異常値,Hは重力測定点の標高,hはΔg_hを求める基準面の高さで,取扱いを簡単にするため,便宜上h≧H_<max>とした.Δg_hはh-Hの空間を密度ρの氷床で埋めた時の,標高hの点でのフリーエア異常値である.南極大陸で測定された重力値を用いて,Δg_<4000>を求めた.その値の変動には大陸の地殻の厚さの反映が見られる.これに着目すると,東南極と西南極では異なったパターンの地下構造であることが分かる. An analytical method is introduced in applying the gravity data to the study of crustal structure by using a reduced gravity anomaly when the thickness of ice sheet is unknown. The reduced gravity anomaly designated as Δg_h(mgal) is defined by the equation of Δg_h=Δg_0-2πGρ(H-h), where Δg_0(mgal) is the free air anomaly, H(m) is the elevation of measurement point and h(m) is the elevation of the point to which gravity anomaly Δg_h should be reduced. The density of ice sheet and the universal constant of gravitation are designated as ρ(g/cm^3) and G respectively. For the practical convenience, the value of h should be taken as constant and larger than or equal to the maximum value of H. The space bounded by the two levels of h and H is assumed to be filled up with ice sheet with density ρ in the reduction procedure. The reduced gravity anomaly Δg_h thus introduced is physically equivalent to the free air anomaly reduced to the points on the surface of ice sheet extending with the constant elevation h. Predominant modes of the spatial distribution of reduced gravity anomalies Δg_<4000> are found in two ranges of wave length, i.e., the shorter wave-length range of 100-200 km and the longer wave-length range of more than l,000 km. The mode of the shorter wave-length range is possibly correlated with topographical features of the rock and ice sheet interface, while the mode of the longer wavelength range is characterized by a decrease of Δg_<4000> toward the inland cart of the continent. The result of the gravity data analysis leads to a conclusion that the crust of the Antarctic ...